2020
DOI: 10.3390/insects11080478
|View full text |Cite
|
Sign up to set email alerts
|

Ecology and Genetic Structure of the Parasitoid Phobocampe confusa (Hymenoptera: Ichneumonidae) in Relation to Its Hosts, Aglais Species (Lepidoptera: Nymphalidae)

Abstract: The biology of parasitoids in natural ecosystems remains very poorly studied, though they are key species for their functioning. Here we focused on Phobocampe confusa, a Nymphalini specialist, responsible for high mortality rates in charismatic butterfly species in Europe (genus Aglais). We studied its ecology and genetic structure in connection with those of its host butterflies in Sweden. To this aim, we gathered data from 428 P. confusa individuals reared from 6094 butterfly larvae (of A. urticae, A. io, an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…While in some systems parasitoid activity can increase with temperature (Mann et al 1990), which could lead to a higher activity period and oviposition rate in the parasitoids at lower and warmer latitude, the literature does not provide consistent evidence of such a pattern (Hawkins 2005). Further, the recorded differences in microclimatic conditions across sites do not align with the latitudinal pattern observed for parasitism (Supplementary material Appendix 1 in Audusseau et al 2020). However, we observed latitudinal differences in the parasitoid community.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…While in some systems parasitoid activity can increase with temperature (Mann et al 1990), which could lead to a higher activity period and oviposition rate in the parasitoids at lower and warmer latitude, the literature does not provide consistent evidence of such a pattern (Hawkins 2005). Further, the recorded differences in microclimatic conditions across sites do not align with the latitudinal pattern observed for parasitism (Supplementary material Appendix 1 in Audusseau et al 2020). However, we observed latitudinal differences in the parasitoid community.…”
Section: Discussionmentioning
confidence: 81%
“…From our study, we cannot rule out the possibility of other spatial confounds causing the differences in parasitism rates across counties. Among the factors not considered here, the differences in parasitoid population dynamics, habitat quality, parasitoids community or the variation in phenological synchrony between the butterflies and their parasitoids (Audusseau et al 2020), may all contribute to the observed decrease in parasitism rates along the latitudinal gradient. For example, the occurrence of other hosts for the parasitoids in the landscape, but not included in our study, may influence the population dynamics of parasitoids and mediate apparent competition (Davis 1991, Gaston et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Other population genetic parameters also indicated that S. mangiferae has low haplotype and nucleotide diversity (Table 2). For instance, the mtDNA nucleotide and haplotype diversity values observed in S. mangiferae are similar to that of a number of other species (Brusentsov et al, 2013;Garcia-Cisneros et al, 2016;Cao et al, 2017;Nakano et al, 2017;Kohli et al, 2018;Audusseau et al, 2020), which were also implicated as possessing low genetic diversity.…”
Section: Discussionmentioning
confidence: 51%
“…The overlap (i.e. temporal co‐occurrence) between the host and its two main parasitoids, Pelatachina tibialis and Sturmia bella , was estimated using the Overlap Parasitoid‐Host index (OPH), as described by Audusseau et al (2020). This index was calculated for all possible combinations of site and year in each region.…”
Section: Methodsmentioning
confidence: 99%